Intravitreal tPA Injection and Pneumatic Displacement for Submacular Hemorrhage in a 10-Year-Old Child - Takayuki Tsuyama; Hiroshi Hirose; Tomohiro Hattori (Case Reports in Ophthalmological Medicine)
Background. Submacular hemorrhage can occur after blunt trauma to the eye. Intravitreal tissue plasminogen activator (tPA) and gas injection are often used for treatment and are effective for submacular hemorrhage caused by age-related macular degeneration. This report describes the clinical outcome in a child with submacular hemorrhage caused by traumatic choroidal rupture who underwent successful intravitreal tPA injection and pneumatic displacement. Case Presentation. A 10-year-old boy developed sudden decrease of vision and a central scotoma in his right eye after trauma. Submacular hemorrhage was found in the eye. Visual acuity was 20/70 OD. Tissue plasminogen activator (12.5 μg in 0.05 mL) and 0.3 mL of pure sulfur hexafluoride were injected into the vitreous cavity under general anesthesia. After surgery, the patient was instructed to maintain a prone position. Displacement of the submacular hemorrhage from the fovea revealed a choroidal rupture, presumed to be the cause of the hemorrhage. After 4 months of follow-up, visual acuity was restored and final visual acuity is 20/16. Conclusion. Intravitreal tPA and gas injection can be an effective treatment for children with submacular hemorrhage.